PERAN PEMERINTAH DALAM PEMBERDAYAAN MASYARAKAT DESA (STUDI PADA DESA SUKAMULYA KECAMATAN PAKENJENG KABUPATEN GARUT PROVINSI JAWA BARAT) - Yana Sahyana (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2017)
This tudy aimed to describe Role of Village Government in Empowering Village Sukamulya Pakenjeng Sub district Garut District, based on the fact, most of livelihood’s Sukamulya Villagers is farm and level of public education in the productive age tends to below. In this study the authors use descriptive research with a qualitative approach. The data collection techniques were observation interviews and documentation. Based on the research that has been done can be concluded that the village government of Sukamulya can empower people through several development program are; The first is activation of the institution, the second is increasing public participation in the implementation of communal work activities, the rsse village musrenbangdes and physical development. The third is increase in productive economic with activity training of black smiths and embroidery. But, in the implementation of an empowerment society, village government Sukamulya had some constrains such as lack of community participation, lazy culture and the of facilities available to support development activities. Keywords: empowerment, village government.